Click chemistry in tuberculosis research: From drug design to therapeutic delivery - A systematic review - Ren, Zimo; Coghi, Paolo (European Journal of Chemistry, 2025)
The molecular hybridization of 1,2,3-triazoles with various bioactive scaffolds has become a promising approach to the development of new antitubercular drugs, offering a versatile platform for improving drug efficacy and specificity. This review covers key advancements over the past decade in creating triazole-based hybrids that integrate azoles, coumarin/chromene, isoniazid, quinoline/dihydroquinoline, quinolone, ferrocene, isatin, furan, and other structures. These hybrid molecules generally show improved potency against both drug-sensitive and drug-resistant Mycobacterium tuberculosis strains while maintaining favorable toxicity profiles, making them particularly valuable in the current landscape of rising drug resistance. Structure-activity relationship (SAR) studies highlight that strategic substituent positioning and optimal linker selection are critical in enhancing antimycobacterial efficacy. Furthermore, modifications to the electronic and steric properties of the hybrids have been shown to influence their ability to bypass common resistance mechanisms, underscoring the potential of these compounds to overcome treatment barriers. In particular, several of these hybrids demonstrate promising activity against MDR-TB and XDR-TB strains, suggesting potential applications for immunocompromised patients, such as those with HIV co-infection. Collectively, these findings offer valuable insights for the rational design of next-generation antituberculosis agents that could transform tuberculosis (TB) treatment paradigms in both resistant and sensitive cases of TB.